Existence of equilibrium in financial markets: Hart's securities exchange model with consumption in the first period (2010)
Hart has established necessary and sufficient conditions for the existence of equilibrium in an economy consisting of two time periods in which agents trade assets whose returns depend on an uncertain state of nature. Hammond has enounced an equivalent condition from an alternative approach to Hart's model. In both cases, it is assumed that agents maximize the expected value of their utility in the second period, when the asset returns are paid. In this paper, Hart's model is modified in such a way that agents also value consumption in the first period and the implications of this modification on the conditions proposed by these authors are analyzed.